1992
DOI: 10.1161/01.hyp.19.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced myogenic responsiveness of renal interlobular arteries in spontaneously hypertensive rats.

Abstract: We recently demonstrated that the interlobular artery (ILA) constricts in response to elevating renal arterial pressure (RAP), suggesting that the ILA contributes to renal autoregulation. In the present study, we examined the segmental myogenic responsiveness of the ILA in kidneys from Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHR). The tapered nature of the ILA allowed us to characterize the regional responsiveness, using the basal diameter to define segments as either proximal (greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…10 In accordance, recent investigations using various approaches demonstrated that increasing RAP elicited ILA constriction. 5,8,18,22 However, the mechanisms mediating autoregulatory responses of ILAs were not fully characterized. Furthermore, differing mechanisms may underlie myogenic responses in distinct segments of ILAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In accordance, recent investigations using various approaches demonstrated that increasing RAP elicited ILA constriction. 5,8,18,22 However, the mechanisms mediating autoregulatory responses of ILAs were not fully characterized. Furthermore, differing mechanisms may underlie myogenic responses in distinct segments of ILAs.…”
Section: Discussionmentioning
confidence: 99%
“…17 Three separate segments, Ϸ10 to 50 m in length, were chosen from an ILA. As described previously, 18 the segments of ILAs were divided into 3 groups according to their basal diameters at 80 mm Hg: proximal(Ͼ60 m), intermediate (40 to 60 m), and distal (Ͻ40 m) ILAs.…”
Section: Methodsmentioning
confidence: 99%
“…The myogenic responses of SHR and WKY afferent arterioles were similar in amplitude but myogenic behaviour was shifted to higher pressures in the SHR. The same group (Hayashi et al 1992) also demonstrated that myogenic responsiveness is enhanced in the intermediate segment of the interlobular artery of SHR kidneys mediated by enhanced calcium channel activity; the increased myogenic activity of the SHR renal vessels might act to prevent or attenuate elevated glomerular pressure. As described by Guyton (1987) renal vascular resistance must increase to permit the development of hypertension otherwise a natriuretic response will rapidly normalise blood pressure.…”
Section: Figurementioning
confidence: 93%
“…Interestingly, whereas in renal arteries of SHR myogenic tone was enhanced, 34 in Dahl (salt-sensitive) hypertensive rats renal microvessels showed impaired myogenic responses, 33 indicating that different mechanisms are present in different forms of hypertension.…”
mentioning
confidence: 99%